New Institutionalism in Cross- Border Cooperation: The Case of Edirne-Kýrklareli Border Region of Turkey - Ervin Sezgin; Gülden Erkut (European Regional Science Association (ERSA), 2015)
Institutions take essential roles in the organization of social life. Ranging from institutionalized informal practices to strict laws and regulations and various public and private organizations, institutions have diffused to day- to- day activities. In this way they do not only regulate social interactions and reduce the transaction costs in the society but also transpose the given social/ political dynamics across different political/ administrative scales. From the supra national scale to the nation- state and to the regional levels this transposition ensures the reproduction of the social structure at these political/ administrative scales. However, institutions also provide a ground for intervention and change, through which the agency of individual and institutional actors intervenes and modifies the wider institutional structure. Therefore the analysis of institutions in any given social setting, enables the researcher i) to map the dynamics of interaction among actors; ii) to understand the wider social/ political and economic factors that affect this setting; and iii) to locate the points of intervention, which through interpretation and invention of methods of resistance allows institutional actors to transcend the structural constrains and to create a unique institutional mechanism. The new institutional theory and especially its three main strands (rational choice, sociological and historical institutionalism) provide a wide array of perspectives for analysing and understanding above-mentioned institutional dynamics. Although these three strands rely on theoretical backgrounds that often contradict with each other; their combined use grasps the diversity and complexity of institutional structures more accurately than using a single approach and excluding the remaining perspectives. Based on a field research conducted in the summer of 2013 at the north-western border region (Edirne- Kýrklareli provinces) of Turkey, this study performs a new institutional analysis for evaluating the major institutional dynamics of cross- border cooperation in the region. For this purpose, various components of the institutional structure of cross- border cooperation are analysed with respect to the three major strands of new institutional theory. The analysis uses the differing theoretical backgrounds of the three strands of new institutionalism to develop a comprehensive understanding of the institutional structure of cross- border cooperation in the region and place it within the wider social/ political structure as well as within the local context. For this purpose the results of the analyses are brought together and discussed in relation to the structure and agency dichotomy. This theoretical conceptualization allows the researcher to find a common ground among the three new institutionalist strands and to use the analysis for establishing a coherent picture of the institutional structure of cross- border cooperation in Edirne- Kýrklareli border region.
Keywords: 330; cross border cooperation; new institutionalism; Edirne- Kýrklareli Border Region